Producing social capital as a development strategy: Implications at the micro-level. (April 2015) - Seferiadis, Anastasia A.; Cummings, Sarah; Zweekhorst, Marjolein B.M.; Bunders, Joske F.G.
This article considers how social capital can contribute to poverty alleviation at the micro-level, based on an analysis of the documentary evidence provided by theoretical perspectives and empirical studies. Across countries and contexts, micro-credit, agricultural production and marketing, environmental protection and knowledge networking are linked to productive social capital. Four mechanisms to strengthen social capital are identified: structural opportunity to meet, 'know-how' of social interaction, sense of belonging and an ethos of mutuality. We envision that opportunities within the development practice exist to foster such mechanisms, and recommend in-depth studies to enhance our understanding of social capital production mechanisms.